Key Considerations for Successful Risk Communication and Community Engagement (RCCE) Programmes During COVID-19 Pandemic and Other Public Health Emergencies - Laston Gonah (Ubiquity Press, 2020)
Risk communication and community engagement (RCCE) is a key pillar in public health emergency response that ensures accurate health information sharing, adoption of protective behaviours by the affected people, and collaborative participation by all stakeholders, including of the local community structures. The success of RCCE programmes rely on strong partnerships and engagement among affiliated groups; clear programme plans and guidelines; establishment of well-laid down coordination structures; and clear measures for reporting and documentation of programme activities. RCCE activities during public health emergencies must put more emphasis on strengthening local structures and communities to ensure active participation of communities in interrupting disease transmission.